Severity of Lesions Involving the Cortical Cholinergic Pathways May Be Associated With Cognitive Impairment in Subacute Ischemic Stroke - Zhong, Huo-Hua; Qu, Jian-feng; Xiao, Wei-Min; Chen, Yang-kun; Liu, Yong-lin; Wu, Zhi-qiang; Qiu, Dong-hai; Liang, Wen-cong (Frontiers in Neurology, 2021)
Purpose: Impairment of cortical cholinergic pathways (CCP) is an important risk factor for chronic vascular cognitive impairment. However, this phenomenon has rarely been studied in post-stroke cognitive impairment (PSCI). We investigated the relationship between PSCI and CCP lesions assessed by structural magnetic resonance imaging (MRI). Patients and methods: We prospectively enrolled 103 patients within 7 days of acute ischemic stroke. CCP was measured by the Cholinergic Pathways Hyperintensities Scale (CHIPS), which semiquantitatively grades MR lesions strategically located on the CCP identified in human brains. We also measured other MRI parameters, including the location and volumes of acute infarcts, cerebral microbleeds, medial temporal lobe atrophy, and white matter lesions. Neuropsychological assessments were performed using the 60-min modified Vascular Dementia Battery (VDB) at 3 months after the index stroke, and PSCI was defined according to VDB, as well as ADL. Results: All 103 patients, 69 men (67.0%) and 34 women (33.0%), with a mean age of 57.22 ± 12.95 years. Fifty-five patients (53.4%) were judged to have PSCI at 3 months, including 43 (41.7%) patients with PSCI-no dementia and 12 (11.7%) patients with post-stroke dementia. According to the VBD assessment, the most commonly impaired cognitive domain was visuomotor speed (27.2%), followed by verbal memory (25.2%). Univariate analysis showed that patients with PSCI were older; had higher Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) scores; had more frequent previous stroke history and atrial fibrillation; and had higher CHIPS scores, more severe white matter lesions, and medial temporal lobe atrophy. PSCI patients also had higher depression scores at 3 months. In the multivariate regression analysis, age, IQCODE score, CHIPS score, and Hamilton Depression Rating Scale score were independent predictors of PSCI. Ordinal regression analysis for risk factors of poor functional outcomes revealed that IQCODE scores and cognitive function status were related to mRS score at 3 months after stroke. Conclusion: In patients with acute ischemic stroke, the severity of lesions involving the CCP may be associated with cognitive impairment at 3 months.